Racial Differences in Contraception Encounters and Dispensing Among Female Medicaid Beneficiaries With Systemic Lupus Erythematosus. Issue 10 (2nd September 2021) - Williams, Jessica N.; Xu, Chang; Costenbader, Karen H.; Bermas, Bonnie L.; Pace, Lydia E.; Feldman, Candace H.
Abstract : Objective: African American and Hispanic women with systemic lupus erythematosus (SLE) have the highest rates of potentially avoidable pregnancy complications, yet racial disparities in family planning among reproductive‐age women with SLE have not been well‐studied. Our objective was to examine whether there are racial differences in contraception encounters and dispensing among US Medicaid‐insured women with SLE. Methods: Using Medicaid claims data from 2000–2010, we identified women ages 18–50 years with SLE. We examined contraception encounters and uptake over 24 months. We used multivariable logistic regression to estimate the odds ratio and 95% confidence interval by race/ethnicity of contraception encounters, any contraception dispensing, and highly effective contraception (HEC) use, adjusted for age, region, year, SLE severity, and contraindication to estrogen. We also compared contraception encounters and dispensing among women with SLE to the general population and women with diabetes mellitus. Results: We identified 24, 693 reproductive‐age women with SLE; 43% were African American, 35% White, 15% Hispanic, 4% Asian, 2% other race, and 1% American Indian/Alaska Native. Nine percent had a contraceptive visit, 10% received any contraception, and 2% received HEC. Compared to White women, African American and Asian women had lower odds of contraception dispensing, and African American women had lower odds of HEC use. Women with SLE were more likely to receive HEC than the general population and women with diabetes mellitus. Conclusion: In this study of reproductive‐age women with SLE, African American and Asian women had lower odds of contraception dispensing and African American women had lower odds of HEC use. Further study is needed to understand the factors driving these racial disparities among this population.